Individual EEG profiling of attention deficits in left spatial neglect: A pilot study. (14th September 2021) - Lasaponara, Stefano; D'Onofrio, Marianna; Pinto, Mario; Aiello, Marilena; Pellegrino, Michele; Scozia, Gabriele; De Lucia, Marzia; Doricchi, Fabrizio
Highlights: Group EEG studies in stroke patients do not capture interindividual variability. We used multivariate EEG analysis to profile individual orienting of attention. We tested right-brain damaged patients with and without neglect and controls. We decoded individual EEG correlates of left and right orienting of attention. These results show that reliable individual EEG profile can be obtained in neglect. Abstract: Electrophysiological group studies in brain-damaged patients can be run to capture the EEG correlates of specific cognitive impairments. Nonetheless, this procedure is not adequate to characterize the inter-individual variability present in major neuropsychological syndromes. We tested the possibility of getting a reliable individual EEG characterization of deficits of endogenous orienting of spatial attention in right-brain damaged (RBD) patients with left spatial neglect (N+). We used a single-trial topographical analysis (STTA; [39] of individual scalp EEG topographies recorded during leftward and rightward orienting of attention with central cues in RBD patients with and without (N−) neglect and in healthy controls (HC). We found that the STTA successfully decoded EEG signals related to leftward and rightward orienting in five out of the six N+, five out of the six N− patients and in all the six HC. In agreement with findings from conventional average-group studies, successful classifications of EEG signals in N+ were observed during the 400–800 ms period post-cue-onset, which reflects preserved voluntary engagement of attention resources (ADAN component). These results suggest the possibility of acquiring reliable individual EEG profiles of neglect patients.